Quantum Dots: An Emerging Approach for Cancer Therapy - Devi, Sheetal; Kumar, Manish; Tiwari, Abhishek; Tiwari, Varsha; Kaushik, Deepak; Verma, Ravinder; Bhatt, Shailendra; Sahoo, Biswa Mohan; Bhattacharya, Tanima; Alshehri, Sultan; Ghoneim, Mohammed M.; Babalghith, Ahmad O.; et al. (Frontiers in Materials, 2022)
Nanotechnology is indisputably a scientific technique that offers the prospect of new therapies, and hope, for the treatment of malignant illnesses. It is a novel technology that offers new approaches for the diagnosis and management of diverse diseases. Although the discovery of Quantum dots (QD) nano-transporters has already led to a few positive developments, QD nano-transporters are still at their initial stage, though have yet proven valuable to society. The excertion of QD indicates conversion in natural imaging along with photograph have established incredible suitability in bio-imaging, new drug development, targeted gene deliverance, biosensing, photodynamic treatment as well as diagnosis. The present review aimed to confer the significance of QD in diagnosis as well as in management of cancer. This review aims to impart fundamental insight as well as conception of QD its merits, properties, utilization as well as mode of action. This review highlight of different designing schemes of QD like hydrothermal, drop-casting, ultrasonic, solvothermal, spin-coating, atomic layer desorption, layer by layer, polymethylmethacrylate aided-transfer, electrochemical, ion beam sputtering deposition. Moreover, we have elaborated on the diverse researches related to cytotoxic examination to reveal that QDs are harmless. Concisely, the present review summarizes the fabrication schemes, current research and utilization of QD in cancer treatment.